2018
DOI: 10.1007/s00170-018-3129-9
|View full text |Cite
|
Sign up to set email alerts
|

Tool wear in dry helical milling for hole-making in AISI H13 hardened steel

Abstract: Helical milling is a hole-making process which can be applied to achieve a high quality finished boreholes in hardened steels. Due to the drilling process limitations, which are intensified when applied in hardened steels, the helical milling process can be applied on hole-making tasks in moulds and dies industry, since milling have been widely applied in moulds and dies machining to replace high-cost operations like grinding and electrical discharge machining. However, to succeed in achieving high-quality bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Chip evacuation is one of the most relevant aspects in composite machining. As mentioned in other studies, such as those carried out by Pereira et al [29] and Wang et al [30], a smaller chip channel could cause the chip to get stuck in the tool, causing an increase in the cutting forces generated during machining. The CFRTP used in this article has a low glass transition temperature and is therefore quite in uenced by the temperature caused by the machining process.…”
Section: An Overview Of Rz Values Measuredmentioning
confidence: 87%
“…Chip evacuation is one of the most relevant aspects in composite machining. As mentioned in other studies, such as those carried out by Pereira et al [29] and Wang et al [30], a smaller chip channel could cause the chip to get stuck in the tool, causing an increase in the cutting forces generated during machining. The CFRTP used in this article has a low glass transition temperature and is therefore quite in uenced by the temperature caused by the machining process.…”
Section: An Overview Of Rz Values Measuredmentioning
confidence: 87%
“…Denkena et al [4] verified that the bottom cutting edge was continuous cutting in the helical milling process, the side edge was intermittent cutting, which was conducive to evacuate chip effectively and reduce the machining temperature, improve tool life, but more prone to _________________________________________________  Haiyan Wang hywang16@126.com 1 School of Control Engineering, Northeastern University at Qinhuangdao, Hebei Province, Qinhuangdao 066004, China show oxidative wear. Pereira et al [5] studied the tool life in dry helical milling of AISI H13 hardened steel, found that wear progressively occurred on the flanks of the frontal cutting edge, and adhesion and oxidation were the main wear mechanisms. For side cutting edges, coating loss and adhesion were observed, as well as fracture on the flanks of the cutting head where the cutting speed was highest.…”
Section: Introductionmentioning
confidence: 99%
“…Also, dry helical milling of AISI H13 hardened steel revealed a possible improvement in productivity. But very high cutting speed resulted in tool nose fracture and largesized burr formation at hole exit [17]. Experimental investigation on helical hole milling of nickel superalloy (MSRR7197) showcased the advantages in terms of lower cutting forces, reduced tool wear, and enhanced surface finish [18].…”
Section: Introductionmentioning
confidence: 99%